Optical and mechanical properties of self-repairing pectin biopolymers - Pierce, Aidan; Liu, Betty S.; Liao, Matthew; Wagner, Willi Linus; Khalil, Hassan A.; Chen, Zi; Ackermann, Maximilian; Mentzer, Steven J. (Polymers, 2022)
Pectin’s unique physicochemical properties have been linked to a variety of reparative and regenerative processes in nature. To investigate the effect of water on pectin repair, we used a 5 mm stainless-steel uniaxial load to fracture glass phase pectin films. The fractured gel phase films were placed on a 1.5-1.8 mm thick layer of water and incubated for 8 h at room temperature and ambient humidity. There was no immersion or agitation. The repaired pectin film was subsequently assessed for its optical and mechanical properties. Light microscopy demonstrated repair of the detectable fracture area and restoration of the films’ optical properties. The burst strength of the repaired film declined to 55% of the original film. However, its resilience was restored to 87% of the original film. Finally, a comparison of the initial and post-repair fracture patterns demonstrated no recurrent fissures in the repaired glass phase films. The water-induced repair of the pectin film was superior to the optical and mechanical properties of the repaired films composed of nanocellulose fibers, sodium hyaluronate, and oxidized cellulose. We conclude that the unique physicochemical properties of pectin facilitate the water-induced self-repair of fractured pectin films.